(untitled) (Asian Journal of Pharmaceutical and Health Sciences, 2021)
Coronavirus disease 2019 (COVID-19) is a contagious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The first case was identified in Wuhan, China, in December 2019. The disease has since spread worldwide, leading to an ongoing pandemic. By this, as a part of break the chain of spreading the disease, home lockdown were implemented all over the world and in India, it was implemented through four phases based on urgency of going out by the people for their basic necessities. Because of this, all people were became panic to go out and as a part of this, parents were afraid to bring their child for providing regular immunization doses which makes to bring more risk for Vaccine Preventable Diseases (VPDs). In this review, we can analyze how Covid- 19 lockdown affected Routine Immunization (RI) in India and mitigation steps taken to overcome this problem in this pandemic situation.